Pelatihan Pembuatan Ecoprint sebagai Inovasi Ramah Lingkungan dan Peningkatan Ekonomi Kreatif Desa Jatijajar - Ahmad Saeroji; Rizqi Aulia Wijayanti; Aulia Rizqi Nugrahaeni (Universitas Negeri Semarang, 2026)
The Tridharma of Higher Education is the basis for academics' contribution to national development, one of which is through the KKN program of Semarang State University in Jatijajar Village, Central Java. Jatijajar Village, with its natural potential and high productive age population, is a strategic location to develop a creative economy based on local resources. One of the programs carried out is training in ecoprint making as a community empowerment effort that is expected to improve the village economy. The method applied in this activity is training and hands-on practice of making ecoprints using natural materials as motifs for totebags. This activity consists of four stages, namely planning and experimentation, preparation, implementation and final or color fixation. The technique used in this training is the pounding technique, which transfers the colors and shapes of plants to the fabric by hitting them. This training also emphasizes the importance of education in providing new skills that can have a positive impact on the social and economic welfare of the village in a sustainable manner.